Mineralization Dynamics of Pineapple Harvest Residues as Affected by Placement on Acrisoil in Benin - Elvire Line Sossa; Codjo Emile Agbangba; Pierre Gbènoukpo Tovihoudji; Jamali Oladédji Ayifimi; Bana Donsaré Nadège Bouko; Oloushègun Isidore Achille Falolou; Guillaume Lucien Amadji (Air, Soil and Water Research)
Pineapple production in Benin is dominated by conventional monocropping with high levels of agrochemicals and the burning of harvest residues. This study aimed at evaluating the decomposition of pineapple harvest residues (PHR) under different modes of placement (surface mulching and burying). A complete random block design with for factor “residues application method” at two levels (surface mulching or burying) and four replications was installed in southern Benin. The residues decomposition was monitored through random sampling of eight litter bags each 60 days for the determination of residual weight, carbon (C), nitrogen (N), phosphorus (P), and potassium (K) contents. A linear mixed-effects model was carried out on the data. The results showed that buried PHR were more rapidly degraded in the soil and the analysis revealed a drop of its K (90%) and P (75%) contents at 4 months after application, while N and C contents decreased slowly until 12 months. Burying at deep of 10 cm can be recommended for direct PHR application to soil. The study highlights the importance of residue management practices in pineapple cultivation and recommends further exploration of methods to optimize the use of PHR in agricultural systems for enhanced soil health and reduced environmental impact.